Effectiveness of Phytomeliorative Measures on Salinized Lands of Southern Karakalpakstan - Abatbay Uli, Bazarbaev Bakhadir (American Journal of Biology and Natural Sciences, 2026)
This article provides a scientific assessment of the effectiveness of phytomeliorative measures on saline and degraded soils in Southern Karakalpakstan — using the example of Tortkul, Beruni, Ellikqala, and Amu Darya districts. Based on field experiments (2021–2024), it was determined that after planting phytomeliorative crops (camelthorn — *Alhagi pseudalhagi*, black saxaul — *Haloxylon aphyllum*, sand rice grass — *Psammochloa villosa*, tamarisk — *Tamarix ramosissima*), soil salinity decreased by 38–56%, the groundwater level dropped by 1.2–2.4 m, and biomass yield reached 3.2–6.8 t/ha. Experiments proved that phytomelioration produces the highest efficiency when combined with comprehensive agrotechnical and hydromeliorative measures. The obtained results have practical significance for addressing desertification and salinization problems in the Aral Sea basin.